Les modernes religioses valencianes: entrebancs d’una recerca textual - Mª. de los Ángeles Herrero Herrero (Scripta: Revista Internacional de Literatura i Cultura Medieval i Moderna)
The catalogue entitled Lletraferides modernes. Catàleg de les escriptores valencianes dels seglesXVI-XVIII (Herrero 2009) provided a starting point for the compilation of Valencian «women ofletters» in the Modern Age. Although this catalogue helped to recover the names of these authors,the process is greatly hindered by the diversity of textual localisation. By considering the differentgenres these writers, particularly the religious authors, favoured (poetry, mystic, spiritual auto/biography,…), this paper aims to provide a number of conclusions for subsequent application inthe sociolinguistic, literary and genre analysis of these works.